Nerve Stimulation Under Ultrasound Guidance Expedites Onset of Axillary Brachial Plexus Block - Shrestha, B R (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE NE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Axillary block is popular technique in upper extremity surgery. Nerve stimulation is used for location of nerves to provide effective blockade. The advent of ultrasound imaging technique in regional anaesthesia has increased the accuracy of needle placement and local anaesthetic deposition around the nerve. The aim of this study is to find out if the nerve stimulation technique with ultrasound guidance has advantages over sole nerve stimulation technique. The outcome measures studied were onset of sensory and motor block, procedure time, number of skin puncture, vascular puncture and paresthesia during nerve stimulation. Methods: This is a prospective randomized comparative study conducted in KMCTH from June 2009 to March 2010 on patients of American Society of Anaesthesiologist I and II requiring upper arm surgery under axillary block. The study comprised of two groups: ultrasound with nerve stimulation group (n=35) and nerve stimulation group (n=35). 24 ml of Bupivacaine 0.5% with injection Dexamethasone 4 mg was used to block the individual four nerves with 6 ml of the local anaesthetic solution per nerve namely ulnar, radial, median and musculocutaneous. The data were recorded by blinded observer. In case of partial block or block failure, the patients were supplemented with Fentanyl or subjected to laryngeal mask placement. Results: Demographic characteristics (age, weight) in either group were similar (p>0.05). The male and female ratio (M: F) in ultrasound with nerve stimulation group was 12:16. The ratio was 18:17 in nerve stimulation group. The onset of complete sensory block was earlier and the onset of motor block was faster in ultrasound with nerve stimulation group than in sole nerve stimulation group (p=0.001). Ultrasound guidance decreased the number of skin puncture during the nerve stimulation, p= 0.02. The incidence of paresthesia was encountered during nerve location (14%), which could be minimized using ultrasound (7%). The success rate of the block was 93% with ultrasound assistance. The procedure time was not different in both techniques. The surgery duration was not significant statistically in either of the group, p=0.715. Conclusions: This study showed that the onset of sensory and motor block was faster with ultrasound assistance nerve stimulation. Complications can be decreased with the use of ultrasound in axillary block. Keywords: axillary nerves, block, motor, sensory, ultrasound.